ANALYSIS OF CRITICAL THINKING ABILITY IN SPLDV - sandi, dian pratiwi maya; Caswita, Caswita (Prima: Jurnal Pendidikan Matematika, 2024)
Critical thinking can be interpreted as processes and abilities used to understand concepts, apply, synthesize and evaluate the information obtained or the information produced . This study aims to describe students' ability to complete SPLDV questions , and find out the causes of the difficulty in solving the SPLDV questions . Research subject consists from 15 students who originate from State Middle School in the district North Lampung . Data study collected through test And interview. Interviews were conducted to complete data about the causes of the difficulty in solving SPLDV problems . The research data were analyzed descriptively . Research result concluded that ability student in finish about SPLDV is at on levels not enough, Enough, And Good, And reason how difficult student finish question SPLDV the is how difficult solving problems with more variables than equations, separating the x and y variables on different sides, and don't get a unanimous solution ( real/imaginary ). In addition, important findings were obtained in this study, namely there are still weaknesses / deficiencies in modifying algebraic forms, look for various alternative problem solving, and separate the two variables (x and y). to students It is advisable to understand the concepts and operations of fractions again, as well as train yourself to be critical in solving them about SPLDV.